Memory in Oral Traditions : the Cognitive Psychology of Epic, Ballads, and Counting-out Rhymes. - Rubin, David C. (Oxford University Press, 1995)
This text applies the methods and theories of cognitive psychology to the study of oral traditions. The author elaborates on three structural devices that appear in oral traditions: those consisting of meaning; those using imagery; and those in which sound pattern is predominant.